1998
DOI: 10.1177/0310057x9802600408
|View full text |Cite
|
Sign up to set email alerts
|

Tracheal Intubation through the Intubating Laryngeal Mask Airway (LMA-Fastrach™) in Patients with Difficult Airways

Abstract: The intubating laryngeal mask airway was used in 31 adult patients in whom tracheal intubation was known or suspected to be difficult. The intubating laryngeal mask airway was successfully inserted in 30 patients and provided a clinically patent airway. In the remaining one patient it was impossible to insert the device correctly. Tracheal intubation through the device was successful in 28 of 30 patients (93%). These results suggest that the intubating laryngeal mask airway has a potential role for tracheal in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
1
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(37 citation statements)
references
References 15 publications
1
33
1
2
Order By: Relevance
“…It has been suggested that the intubating laryngeal mask airway is likely to be particularly effective in cases where direct laryngoscopy is expected to be dif®cult [4,17,18]. Since its introduction, it has proved to be an effective device and conduit for blind intubation of the trachea and ventilation of the lungs [3±7].…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the intubating laryngeal mask airway is likely to be particularly effective in cases where direct laryngoscopy is expected to be dif®cult [4,17,18]. Since its introduction, it has proved to be an effective device and conduit for blind intubation of the trachea and ventilation of the lungs [3±7].…”
Section: Discussionmentioning
confidence: 99%
“…This technique has been shown as a successful backup intubation tool after other intubation techniques have failed,[89] or in patients with difficult airway or conditions that result in limited access to the patient's airway. [1011]…”
Section: Airway Managementmentioning
confidence: 99%
“…However, the success rates for blind intubation in children weighing at least 25 kg is about 66% on first attempt. 70,71 In a study of 193 intubations performed on patients aged 11 to 89 years with at least one of the following: failed intubation associated with grade 4 Cormack-Lehane view, cervical spine immobilization, distortion of the airway, or a stereotactic head frame, the ILMA provided successful blind intubation in 76% of cases on the first attempt, 14% on the second, and 4% on the third attempt. 65 -68 Under cinefluoroscopy, insertion of the ILMA (and the LMA) results in significantly less posterior displacement of a destabilized C-3 segment in a cadaver model when compared with endotracheal intubation under direct laryngoscopy.…”
Section: Complicationsmentioning
confidence: 99%